The Effectiveness of the Supplementary Feeding Program (PMT) in Improving the Nutritional Status of Toddlers in Bulo Village - -, Herick - (Tadulako University, 2025)
Nutritional problems among toddlers remain a significant public health concern in Indonesia, including in Bulo Village, which has shown a fluctuating trend of undernutrition and overnutrition over a three-month period. This study aims to evaluate the effectiveness of the Supplementary Feeding Program (PMT) in improving the nutritional status of toddlers in Bulo Village. This research employed a quantitative method with a quasi-experimental design using a pre-test and post-test approach without a control group. The sample consisted of 116 toddlers aged 12–59 months who received supplementary feeding for four months. Data were collected through anthropometric measurements (weight and height) and a questionnaire assessing mothers' nutritional knowledge, both before and after the intervention. Data analysis was conducted using paired t-tests for normally distributed variables and the Wilcoxon signed-rank test for non-normally distributed variables. The results indicated a significant improvement in toddlers' height (p = 0.000) and weight (p = 0.000) after the PMT intervention. Additionally, there was a significant increase in maternal nutritional knowledge (p = 0.000). These findings suggest that the Supplementary Feeding Program is effective in enhancing both the nutritional status of toddlers and the awareness of mothers in Bulo Village. This intervention should be considered for long-term implementation to address nutritional issues among children. Keywords : Toddler ; Supplementary Feeding ; Nutritional Status